Teachers' conceptualisation of the learning needs of pupils with cochlear implants in Dar es salaam's inclusive primary schools, Tanzania - Kisanga, Sarah Ezekiel; Foya, Zamoyoni Ozeniel (Papers in Education and Development, 2024)
This study employed a multiple case study design to examine teachers' awareness of the learning needs of pupils with deafness using cochlear implants (PCIs) in inclusive primary schools in Dar es Salaam, Tanzania. Data were collected from 25 participants through semi-structured interviews and observations and analysed thematically. The findings revealed that most teachers had limited knowledge of cochlear implants and the specific learning needs of PCIs, with only a few demonstrating adequate understanding. Teachers with special education training showed greater awareness than their counterparts in general inclusive schools. To bridge this gap, the Ministry of Education, Science, and Technology (MoEST) and the Tanzania Institute of Education (TIE) should integrate cochlear implant education into teacher training programmes. Furthermore, school management is encouraged to implement continuous professional development in collaboration with cochlear implant specialists to enhance teacher capacity in supporting PCIs.